Phosphorus fertilization regimes and rates alter Cd extractability in rhizospheric soils and uptake in maize (Zea mays L.). (July 2022) - Wang, Yongzhuang; Peng, Xiangying; Lai, Liuying; Li, Hao; Zhang, Xinying; Chen, Hongxing; Xie, Lingtian
Abstract: Understanding cadmium (Cd) extractability and transfer in soil-plant system is crucial for the evaluation of the remediation effect of Cd-contaminated soils. However, knowledge on the effects of different phosphorus (P) fertilizers on Cd uptake in plants, root morphology, and Cd extractability in rhizosphere soils remains very limited. In this study, a five-year field experiment was conducted to evaluate the impacts of four P fertilizers (i.e. calcium superphosphate, calcium magnesium phosphate, monopotassium phosphate, and compound fertilizer) on Cd uptake in maize ( Zea mays L.), root morphology, and Cd extractability in rhizospheric acidic soils contaminated with Cd. The results showed that compared to the control, the contents of rhizospheric DTPA-Cd were respectively 18–40% and 8–29% lowered by the calcium magnesium phosphate and monopotassium phosphate, but 21–59% and 10–36% elevated by the calcium superphosphate and compound fertilizer. Similar effects of P fertilizers were observed on exchangeable Cd. Furthermore, the altered levels of the DTPA-Cd and exchangeable Cd in the rhizospheric soils were greater than those in the non-rhizospheric soils. Moreover, different P fertilization regimes altered the contents of Cd in maize tissues (roots, stems, leaves, and grains), and the alterations were closely related to the variation of DTPA-Cd and exchangeable Cd in the rhizospheric soils. Meanwhile, different P fertilization regimes enhanced root morphological parameters (root length, surface area, and volume), and the activities of urease and surcase. In general, the lowest concentrations of soil DTPA-Cd and Cd in maize tissues were found in the treatments with calcium magnesium phosphate. This study has demonstrated that the calcium magnesium phosphate can be used as a potential amendment agent for the acidic Cd-contaminated soils cultivated with maize. Graphical abstract: Image 1 Highlights: P fertilizers affect the rhizospheric and non-rhizospheric DTPA-Cd and Cd fractions. Changes in DTPA-Cd are greater in rhizospheric soils than in non-rhizospheric soils. P fertilizers affect corn Cd uptake by altering soil DTPA-Cd and exchangeable Cd. P fertilizers elevate activities of urease and surcase in Cd contaminated soils. Calcium magnesium phosphate is optimal for Cd-contaminated soils planted with maize.